Application reference architecture in public clouds - Katajamäki, Anna (My University, 2014)
Interest towards cloud computing and its usage in companies core processes has been rising during the last decade. Cloud computing is already a common phenomenon among ordinary consumers and one can run into them almost daily for example by using Google’s services. But when it comes to companies, there are still many challenges and prejudices of cloud computing to be solved before companies can utilize it. The aim of this thesis is to build application reference architecture in public cloud. The research questions are investigating what one has to take into consideration when moving applications to public cloud. The other question where this thesis concentrates is standards and principles in cloud computing and if there are any changes or challenges regarding them. The research was based on market analysis that consisted of three biggest service providers in the market that were investigated in detailed way. Three smaller providers were also introduced only superficially. Using different sources like websites, articles and news, the information of service providers was collected. As a result, gaps between the current applications and requirements for the cloud environment were found. Many of them were related to the fact that service provider is responsible for the platform and customer only for the application. These gaps should be solved before moving applications to cloud. Standardization is also needed since at the moment there is not one single source that everyone is following. It will also help customers for example to change cloud service provider easier when all of them are following the same standards. At the moment, the standards have to change quite a lot from the current state.
Keywords: cloud computing; public cloud; application reference architecture; fi=Tietotekniikka (KTM)|en=Computer Science|; fi=Tietotekniikan koulutusohjelma (DI)|